Mardi Goena, Krida Beksa Wirama, and Harbiranda: Skilful Hand of KRT Jayadipura in Developing and Preserving the Javanese Culture, 1920s to 1930s - Indra Fibiona; Siska Nurazizah Lestari (Diponegoro University, 2017)
Ethical politics proclaimed by the colonial Government especially in education has made a room for the society in colonial Territories to preserve their culture. In addition, the idea of restoring the Javanese culture as a noble culture is mainly raised by the educated Dutch-Javanese nationalists at the beginning of XX century. The condition then triggered the elite royal (keraton) as well as artists to compete in the restorations and refinements. One of the elite royals and keraton Yogyakarta artists with his skilful hand, KRT Jayadipura tried to restore and refine Javanese traditional art in order to return the noble value of Javanese culture. His contribution in traditional art flows through Mardi Goena, Krida Beksa Wirama, and Harbiranda. KRT Jayadipura KRT works enjoyed by both local and international public. Therefore, the Javanese culture especially the noble art can be widely known and raises the public awareness of Java to continue to preserve it.